Evolution of Rolls-royce Air-cooled Turbine Blades and Feature Analysis. (2015) - Xu, Li; Bo, Sun; Hongde, You; Lei, Wang
Abstract: During past few decades there has been significant increase in turbine entry temperature (TET) in order to improve gas turbine ability and efficiency, which represents a huge challenge to turbine blades. Rolls-Royce maintains world-leading technology and capability in gas turbines design and manufacture, this study mainly focuses on the evolution of air-cooled turbine blades fabricated by Rolls-Royce, which shows that turbine blade developments are increasingly dependent on the improvement of material science and blade cooling technology. Moreover, its unique blade tip designs which minimize over-tip leakage are also reviewed. Future developments to improve turbine blade ability and reliability including high temperature materials, blade cooling technology and CFD analyzing approach are discussed.